Food and Feeding Habits of a Bentho-Pelagic Fish, Garra paralissorhynchus (Vishwanath & Shanta, 2005) from Manipur, India - PRABINA, SALAM; RAMESHORI, YUMNAM; PANDEY, PRAMOD KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The gut content of Garra paralissorhynchus (Vishwanath & Shanta, 2005), a bentho-pelagic fish inhabiting the fast-flowing streams were studied. Specimens were collected seasonally from the hill streams of Manipur, and dietary analysis was conducted using gut content examination and gut length measurement. Gut content analysis revealed that G. paralissorhynchus diet primarily consisted of Bacillariophyceae, Chlorophyceae, and Zygnemophyceae, along with miscellaneous food items, highlighting the herbivorous and plankty-herbivorous feeding habits of the fish. Bacillariophyceae species dominated the gut content with Amphora sp. as the most preferred food items. The relative gut length (RGL) of the species varied from 3.195 to 5.063 across different size groups, confirming its adaptation to an algal diet. Feeding intensity fluctuated seasonally, with the highest activity during March–May (67.02 % active feeding), likely due to pre-breeding energy demands, and the lowest during June–August (20.83% active feeding), coinciding with the spawning period. Seasonal variations in feeding intensity and diet composition were linked to food availability and physiological changes during reproductive phases. Comparisons with other Garra species and freshwater fishes indicated that the diet composition also varied significantly. The findings indicate the seasonal variation in the diet of G. paralissorhynchus is correlated with fluctuations in plankton availability reflecting the interaction between the trophic behaviour and environmental conditions. This research contributes to understanding the species biology, aiding in the development of effective conservation and ecosystem-based fisheries management strategies within the ecologically sensitive and biodiverse riverine systems of Northeast India.